Wellness program for FNRI employees (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2005)
In support to the healthy and active lifestyle campaign in the office setting, the FNRI organized and conducted a Wellness Program to promote a healthy lifestyle among its employees. Specifically, the program aimed to (1) evaluate the health status of the employees, (2) identify the health risks and needs of the employees, and (3) recommend an appropriate nutrition action plan, To determine whether the program achieved the desired effects, an evaluation of the health behavior and health status of the participants was conducted. Height, weight, body mass index (BMI), and blood pressure were taken among 34 male and 140 female employees, aged 21 to 65 years, using standard measuring techniques. A self-administered health history questionnaire was used to assess their risk of developing coronary heart disease. The data obtained from the questionnaire were used to group the participants. Those with risk factors were assigned to Group I and those without, to Group II. Group I underwent lipid and fasting blood sugar (FBS) determination, individual dietary counseling, and physical activity regimen such as brisk walking and aerobic. Group II joined the group dietary instruction and engaged in aerobic, table tennis, badminton, and basketball. Impact evaluation of the program was assessed in terms of changes (before and after the program) in BMI, blood chemistry, blood pressure, physical activity, and eating habits. Among the participants, it was observed that the proportion of overweight and obesity decreased from 41.6% to 40.3%. An improvement in the FBS, LDL-c, and blood pressure of the at-risk group taking medicines was observed. However, no improvement was observed in the total cholesterol, HDL-c, and triglyceride level. Improved physical activity and eating habits were noted. Using a self-administered questionnaire, results of the evaluation done on the program's impact on improved health behavior and health status revealed that the participants became more careful in their choice of nutritious foods, exercised more, felt better, and became more productive in their work. The study suggests that developing a suitable wellness program and adapting it successfully could bring about lifestyle changes necessary to improve the health status and reduce the onset and complications of chronic diseases.